Implementing a One Health approach to emerging infectious disease: reflections on the socio-political, ethical and legal dimensions. (December 2015) - Degeling, Chris; Johnson, Jane; Kerridge, Ian; Wilson, Andrew; Ward, Michael; Stewart, Cameron; Gilbert, Gwendolyn
Abstract Background 'One Health' represents a call for health researchers and practitioners at the human, animal and environmental interfaces to work together to mitigate the risks of emerging and re-emerging infectious diseases (EIDs). A One Health approach emphasizing inter-disciplinary co-operation is increasingly seen as necessary for effective EID control and prevention. There are, however, socio-political, ethical and legal challenges, which must be met by such a One Health approach. Discussion Based on the philosophical review and critical analysis of scholarship around the theory and practice of One Health it is clear that EID events are not simply about pathogens jumping species barriers; they are comprised of complex and contingent sets of relations that involve socioeconomic and socio-political drivers and consequences with the latter extending beyond the impact of the disease. Therefore, the effectiveness of policies based on One Health depends on their implementation and alignment with or modification of public values. Summary Despite its strong motivating rationale, implementing a One Health approach in an integrated and considered manner can be challenging, especially in the face of a perceived crisis. The effective control and prevention of EIDs therefore requires: (i) social science research to improve understanding of how EID threats and responses play out; (ii) the development of an analytic framework that catalogues case experiences with EIDs, reflects their dynamic nature and promotes inter-sectoral collaboration and knowledge synthesis; (iii) genuine public engagement processes that promote transparency, education and capture people's preferences; (iv) a set of practical principles and values that integrate ethics into decision-making procedures, against which policies and public health responses can be assessed; (v) integration of the analytic framework and the statement of principles and values outlined above; and (vi) a focus on genuine reform rather than rhetoric.